The effect of secondhand smoke exposure on dental caries and gingival health among schoolchildren in Damascus, Syria: a cross-sectional study - Ghalia Misrabi; Mawia Karkoutly; Nada Bshara (BMC, 2023)
Abstract Objective This study aimed to evaluate the effect of secondhand smoke on dental caries and gingival health among schoolchildren in Damascus, Syria. Materials and methods This was a cross-sectional study. It was carried out at government schools in Damascus, Syria. This study included healthy children aged 10 to 13 years old. Schoolchildren were interviewed to answer the researcher-administered questionnaire to obtain answers regarding demographic information and family smoking behavior. A dental examination was performed by a dentist, and the number of decayed (D), missing (M), and filled (F) permanent teeth (DMFT) was scored based on the World Health Organization (WHO) 1997. A gingival examination was performed using the modified gingival index (MGI) and Silness-Leo plaque index (PI) to assess gingival inflammation and plaque accumulation, respectively. Results A total of 284 schoolchildren participated. More than half (61.26%) of them were exposed to secondhand smoke (SHS), and about half of them (52.11%) resided in a house with at least one cigarette smoked in a day. About one-third of the passive smokers (33.30%) had poor plaque control, with a statistically significant difference from non-passive smokers (p < 0.05). The multivariate regression model showed that the number of smokers at home was significantly associated with the DMFT score, dental plaque accumulation, and gingival inflammation (p < 0.1). However, the number of cigarettes smoked at home in a day was not a predictor for dental caries and gingival status (p = 1.000). Conclusions Within the limitations of this study, the number of smokers at home appears to have more adverse effects on children's oral health compared to the quantity of smoke inhaled. In addition, SHSe was associated with more dental plaque accumulation among schoolchildren.